Towards service-based approach: building huge software architectural design. (11th February 2011) - Dbouk, Mohamed; Sbeity, Ihab; Mcheick, Hamid
Software architecture, as a discipline, draws vocabulary like rules, paradigm, pattern that help to build software systems. In this paper we first provide an introduction to the emerging field of software architecture. Many software architecture approaches were introduced; they draw different paths and methodologies to build software systems. This paper forms a survey for some of these approaches with a focus on the decomposition approach in terms of requirements and data-attributes. In this paper we will discuss a new formal service-based software decomposition approach. This approach consists of a micro-phased process. We begin by considering the front-end services, the common and modern architectural styles upon which many systems are currently based; we focus on their business profiles, non-atomic business data-items and business rules. Our proposed approach represents the first and crucial design stage in the software engineering process. It consists of building the overall software architectures that could be represented as an oriented and purposed graph. At the end, we demonstrate that the process is plausible and easy to apply. We also state that micro-phases may be reiterated and executed without strict ordering. Meta-modelling and computerising such approach represents our future works.